2018
DOI: 10.1039/c7ra12364g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduced graphene oxide on the growth, structure and decomposition activity of white-rot fungus Phanerochaete chrysosporium

Abstract: Graphene materials have attracted great interest nowadays due to their large-scale production and wide applications. It is urgent to evaluate the ecological and environmental risk of graphene materials for the healthy development of the graphene industry. Herein, we evaluated the influence of reduced graphene oxide (RGO) on the growth, structure and decomposition activity of white-rot fungus, whose decomposition function is vital for carbon cycle. RGO slightly stimulated the fresh weight and dry weight gains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…The influence of graphene derivatives on the viability of other fungi has been little studied. Recently, two studies reported the impact of graphene oxide and reduced graphene oxide on the filamentous fungus Phanerochaete chrysosporium, with the latter compound showing lower toxicity for the fungus than the former 42,43 . Besides carbon nanomaterials, the toxicological impact on S. cerevisiae of various metal oxide nanoparticles have been evaluated as well, generally showing low toxicity [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of graphene derivatives on the viability of other fungi has been little studied. Recently, two studies reported the impact of graphene oxide and reduced graphene oxide on the filamentous fungus Phanerochaete chrysosporium, with the latter compound showing lower toxicity for the fungus than the former 42,43 . Besides carbon nanomaterials, the toxicological impact on S. cerevisiae of various metal oxide nanoparticles have been evaluated as well, generally showing low toxicity [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…The viability of S. cerevisiae cells exposed to two GN concentrations (160 and 800 mg L −1 ) and exposure times (2 and 24 h) was assessed through colony forming units (CFU) determination. The concentrations selected to assess the biological impact of GN on yeast cells were based on previous concentration ranges used by other authors in recent studies, where the impact of distinct graphene derivatives on fungal species was studied [41][42][43][44] . Also, a previous study provided toxicology data at transcriptomics level by exposing S. cerevisiae to 160 mg L −1 45 , so we considered interesting to use the mentioned concentration to assess and compare the toxicological response…”
Section: Determination Of Colony Forming Units S Cerevisiae Cells Exmentioning
confidence: 99%
“…Upon chemical reduction, RGO stimulated the fresh weight gain of P. chrysosporium at 0.25 mg/mL and higher. A meaningful dry weight stimulating effect was observed at RGO concentrations of 1.0 mg/mL and higher [ 31 ]. Huang et al reported that Fe 3 O 4 nanoparticles (NPs) slightly inhibited the biomass gain of P. chrysosporium at 0.5 mg/mL after 1 d exposure and stimulated the biomass gain at day 3 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xie et al reported that graphene oxide (GO) inhibits the growth of white rot fungi and leads to the complete loss of degradation activity for dye [ 27 ]. Yang et al suggested that chemical reduction alleviates GO effects on white rot fungi [ 31 ]. After reduction by vitamin C, reduced GO (RGO) does not suppress the degradation activity of white rot fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation